Effects of Porous Media on the Convective Heat Transfer in Nanofluid-Based Photovoltaic/Thermal System - Alzamili, Hanan S.; Hussain, Hazim H.; Mahdi, Raed Abed (Iraqi Journal of Science, 2025)
The convective heat transfer and nanofluid flow through porous media within the Photovoltaic/Thermal system (PV/T) under maximum air temperatures of 10, 25, and 52 οC in Baghdad city were investigated numerically. The PV/T system was filled with porous media and nanofluid, where the porous media consisted of open-cell aluminum foam (6101-T6 alloy) with a pore density of 20 PPI and a porosity of 0.9353-0.92%. The nanofluids were composed of aluminum oxide (Al2O3) and silicon dioxide (SiO2) nanoparticles suspended in water and ethylene glycol (EG) with a volume fraction of 1-3 % and a nanoparticle diameter of 25 nm. A high-efficiency solar panel with a thermal collector was used at tilt angles of 0ο, 10ο, 30ο, 45ο, and 90ο. The Finite-Volume Method (FVM) was employed to solve the governing equations of momentum, continuity, and energy. The study examined the effects of porous media and nanofluid properties, as well as tilt angles, on the performance of the PV/T system. The findings indicate that the highest heat transfer coefficient was attained when employing Al2O3-water nanofluids and aluminum foam at a PV/T tilt angle of 90ο. The heat transfer coefficient increased with the PV/T tilt angle, nanoparticle volume fraction, and Reynolds number, while it demonstrated a decrease with porosity. An increase in the Reynolds number from 600 to 1700 resulted in a 6% enhancement in the heat transfer coefficient. Conversely, an increase in porosity led to an approximate 1% decrease in the average heat transfer coefficients. Using water as the base fluid improved the heat transfer coefficient by 6% compared to EG. Additionally, as the tilt angle increased from 0⁰ to 90⁰, the heat transfer coefficient experienced a 2.5% enhancement. The combination of nanofluid with aluminum foam improved the thermal efficiency compared to nanofluid and base fluids alone. Moreover, the thermal efficiency remained consistent with an increase in heat flux.